Pengaruh Penempatan Produk di Kasir dan Sales Person terhadap Impulse Buying - Dian Tauriana; Ika Fietrin (The Winners, 2011)
Product placement in the cashier and using sales person have important effects for impulse purchasing in a retail that will increase company selling. The purpose of this research is to acknowledge product placement influences in cashier and sales person towards buying impulse in GIANT hypermart in Plaza Semanggi, Jakarta. The research is associative research. Data collecting technique is done by spreading questionnaire to consumers in GIANT Hypermart Plaza Semanggi and interview with the management. Data analysis technique is by validation and reliability test, normality, simple and double regression test with software SPSS 16.0. The research result shows that the product placement variable in cashier and sales person influenced simultaneously and significantly to impulse buying.